The Effectiveness of Using Paired Storytelling Technique Towards the Students’ Reading Comprehension - Yohana Puspita, Dewi (International Journal Corner of Educational Research, 2022)
This research aimed to find out whether: (1) the paired storytelling technique is more effective than the conventional technique to teach reading; (2) the average score of students’ reading comprehension who learn reading through the paired storytelling technique is higher than those who learn reading through the conventional technique. The population was the second semester students of SMA Muhammadiyah Prambanan which consist of 77 students. Purposive sampling was used to determine the experimental class and control class. Each class consists of 26 students. The experimental class was treated by using paired storytelling technique, while control class was treated by using conventional technique. Then, the technique which was used to collect the data were multiple choice test for getting the data of students’ reading skill. The instrument of reading test was tried out to get the validity and reliability items. The data from post test were tested their normality and homogeneity. It was found out that the data were normal distribution and homogeneous. After that the data were analyzed to get the hyphothesis test by using ANCOVA.